Optimization of film over nanosphere substrate fabrication for SERS sensing of the allergen soybean agglutinin. (4th November 2020) - Styles, Matthew J.; Rodriguez, Rebeca S.; Szlag, Victoria M.; Bryson, Samuel; Gao, Zhe; Jung, Seyoung; Reineke, Theresa M.; Haynes, Christy L.
Abstract: Metal film over nanosphere (FON) substrates are a mainstay of surface‐enhanced Raman scattering (SERS) measurements because they are inexpensive to fabricate, have predictable enhancement factors, and are relatively robust. This work includes a systematic investigation of how the three major FON fabrication parameters—nanosphere size, deposited metal thickness, and metal choice—impact the resulting localized surface plasmon resonance (LSPR). With these three parameters, it is quite simple to fabricate FONs with an optimal LSPR for SERS experiments with various excitation wavelengths. Some SERS experiments require that the substrates be incubated in organic solvents that have the potential to damage the substrate; as such, this work also explores how solvent incubation impacts the physical and optical properties of the FON substrate. Although no significant increase in physical damage is obvious, the LSPR does shift significantly. Finally, these optimized FONs were employed for the sensing of an important allergen, soybean agglutinin. The FONs were modified with a glycopolymer that has affinity for soybean agglutinin and clear Raman bands demonstrate detection of 10 μg/ml soybean agglutinin. Overall, this work serves the dual purpose of both sharing critical details about FON design and demonstrating detection of an important lectin analyte. Abstract : This work studies the optimization of metal film over nanosphere SERS substrates for biosensing applications. The noble metal used, size of packed spheres, and solvent stability all play a role in optimizing these substrates. Herein, we focus on sensing a soybean agglutinin protein with a linear glycopolymer attached at the substrate surface and monitor binding via SERS.